Canada: Playing catch-up on phosphorus policy - Jessica Zane Ross; Sidney Omelon (Canadian Science Publishing, 2018)
The concept of sustainable phosphorus is studied in depth around the world, as the scientific community largely agrees that the non-renewable phosphorus reserves in the form of phosphorite ore must be used judiciously. Unfortunately, many developed countries, including Canada, have yet to implement a phosphorus management plan. The Netherlands, Germany, and Switzerland can be heralded as success stories of effective, committed, cross-sector phosphorus management. We examine factors that contributed to their success and consider how these may be transferred to Canada. We also consider Canadian geographic and research factors and contrast the Canadian policy environment and phosphorus recycling efforts with those in the EU. Finally, we analyze active Canadian and North American phosphorus interest groups and seek to determine why their collective efforts have yet to coalesce around tangible action. Canada produces phosphorus fertilizer from imported deposits of phosphate rock. Canada produces potassium fertilizer from its rich potash mines, making it a global power in nutrient production. It is imperative that Canada earns a respected leadership role in efficient global phosphorus and potassium nutrient management and recycling.